Violence against women: characterization of cases in monitoring of a municipal reference center (Research, Society and Development, 2020)
Introduction: In Brazil, the number of women who suffer domestic violence has increased significantly. They were registered in the Mortality Information System (SIM) in 2016, where 57,395 deaths were of women due to aggression. Objective: to characterize the cases of violence against women followed up at a municipal reference center in Teresina - PI. Methodology: Retrospective documentary study, with a descriptive quantitative approach carried out at the Reference Center for Women in Situations of Violence Esperança Garcia in 2019. The sample consisted of 120 medical records of women. The medical records of women over 18 years of age were included and only those who had incomplete information were excluded. For data collection, a questionnaire with closed questions was used. The data were analyzed using the SPSS version 20 program. Results: The study showed that women who suffered violence were aged between 29 and 38 years old (35.3%), mixed race (85.8%), average level of education (44.1%), in stable union (42.5%), unemployed (42.5%), with their own home (70.8%), heterosexual behavior (100%). As for the type of violence, 100% suffered psychological violence, 84.1% moral and 65.8% physical. The assaults occurred more than a year ago, at home, and most cases happened because they no longer wanted to live with the aggressor as for the aggressor, 33.33% were between 39 and 49 years old, 95% were brown, 62.5% worked, 29.1% were the victim's companions and 46.67% were not on any drugs. Conclusion: There is a need for the engagement of different sectors of society to ensure that all women have their rights preserved. It is hoped that with the data obtained in the research they will be able to collaborate with the Public Policies of effective coping mainly in the state of Piauí, which has presented alarming data on violence against women.